1983
DOI: 10.1021/np50027a025
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical Study of Some Cassia Species Cultivated in Egypt

Abstract: Plants of the genus Cassia are rich in polyphenol and anthraquinone content.Cassia javanica Linn., C. didymobotrya Fres, and C. nodosa Buch-Ham. are recorded to have many medicinal uses (1).C. javanica Linn, was the subject of many studies (2-6), while C. didymobotrya and C. nodosa were studied only preliminarily (7,8). A variation in the components present in C. javanica cultivated in Egypt with those reported previously instigated this investigation. RESULTS AND DESCUSSIONThe ether fraction of the ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Powdered pods are applied topically to various parts of the body to decrease body temperature and to bleeding sites to stop hemorrhage. Chemical analysis of the pods revealed the presence of tannins, the most important of which are gallic acid (3,4,-5-tetrahydrobenzoic acid, m-digallic acid, catechin and some galloyalated flavans (Goodwin and Nurstem, 1973;El-Sayyad, 1983;Gupta et al, 1981;Gupta and Bokadia 1975). In vitro studies using the pods' tannin have shown that it has an antiviral and antifungal activity against Piricularia oxyzae (Fischer et al, 1954;Baruah et al, 1963).…”
mentioning
confidence: 99%
“…Powdered pods are applied topically to various parts of the body to decrease body temperature and to bleeding sites to stop hemorrhage. Chemical analysis of the pods revealed the presence of tannins, the most important of which are gallic acid (3,4,-5-tetrahydrobenzoic acid, m-digallic acid, catechin and some galloyalated flavans (Goodwin and Nurstem, 1973;El-Sayyad, 1983;Gupta et al, 1981;Gupta and Bokadia 1975). In vitro studies using the pods' tannin have shown that it has an antiviral and antifungal activity against Piricularia oxyzae (Fischer et al, 1954;Baruah et al, 1963).…”
mentioning
confidence: 99%
“…The study showed that an acacia diet significantly decreased weight gain in animals suggesting the presence of growth impairing substances in acacia pods. High levels of tannin in acacia leaves and pods have been widely reported (Goodwin and Nurstem, 1973;Gupta et al, 1981;El-Sayyad and Ross, 1983;Sotohy et al, 1995 and1997). In addition, Sotohy et al (1997) observed that the digestion coefficients of most nutrients were significantly decreased in goats fed 5% to 20% acacia diets.…”
Section: Discussionmentioning
confidence: 98%
“…El- Sayyad and Ross (1983) reported the isolation of a phenylpropanoid compound, sinapic acid, from the ethanol extract of leaves of C. javanica while four phenylpropanoid compounds such as cinnamic acid, 1-(4-hydroxy-3,5-dimethoxyphenyl)-propan-1-one, 3-hydroxy-1-(4-hydroxy-3-methoxyphenyl)-propan-1-one, and 2,3-dihydroxy-1-(4-hydroxy-3-methoxyphenyl)-propan-1-one were isolated from the dichloromethane extract of C. laevigata leaves (Jones, Bartholomew, Vaishnav and Gupta (1996) 5-Hydroxy-1,4,6,7-tetramethoxy-2-methylanthraquinone Gonza, Barrera, Davila, Valencia, and Domi (1992) 1,5,7-Trihydroxy-4,6-dimethoxy-2-methylanthraquinone Gonza et al (1992) 5,6-Dihydroxy-4,7dimethoxy-2-methylanthraquinone Gonza et al (1992) 5,7-Dihydroxy-l,4,6-trimethoxy-2-hydroxy methylanthraquinone Gonza et al (1992) 5-Hydroxy emodin C. javanica RB/M Tiwari and Singh (1979) 1,3,5,8-Tetrahydroxy-6-methoxy-2-methyl anthraquinone C. javanica HW/M Singh and Singh (2008) 1,3-Dihydroxy 6,8-dimethoxy-2-methyl anthraquinone Gupta, Agrawal, Singh, and Tiwari (1989) 1,3-Dihydroxy-6-methoxy-7-methylanthraquinone Sekar, Prasad, Sidduraju, and Janardhanan (1999) Gupta et al (1989) Sengulone C. multiglandulosa a L/Ch Kitanaka and Takido (1994) (Continues)…”
Section: Phenylpropanoids and Xanthonesmentioning
confidence: 99%
“…El‐Sayyad and Ross (1983) reported the isolation of a phenylpropanoid compound, sinapic acid, from the ethanol extract of leaves of C . javanica while four phenylpropanoid compounds such as cinnamic acid, 1‐(4‐hydroxy‐ 3,5‐dimethoxyphenyl)‐propan‐1‐one, 3‐hydroxy‐1‐(4‐hydroxy‐3‐methoxyphenyl)‐propan‐1‐one, and 2,3‐dihydroxy‐1‐(4‐hydroxy‐3‐methoxyphenyl)‐propan‐1‐one were isolated from the dichloromethane extract of C .…”
Section: Phytochemistrymentioning
confidence: 99%